A Label-Free Aptasensor for the Detection of Ochratoxin A Based on Competitive Molecule-Level Interactions. Issue 14 (18th November 2020) - Qiao, Xiujuan; Wang, Yahui; Arsalan, Muhammad; Yang, Shuying; Wang, Yuan; Sheng, Qinglin; Yue, Tianli
Abstract : A simple and label-free aptasensor for rapid determination of ochratoxin A (OTA) has been proposed, which is based on the competitive strategies between single stranded DNA (ssDNA) and methylene blue (MB) on two-dimensional (2D) nitrogen-doped graphene (NGE) surfaces. Compared with the binding force of electrostatic attraction and weak π - π stacking between MB and NGE surfaces, the binding affinity of hydrogen bonding and stronger π - π stacking will contribute to the binding force between ssDNA nucleobases and graphene. As mentioned above, the combination of aptamer with OTA can release complementary DNA (cDNA) to detection system and the single stranded cDNA thus attaches to NGE surfaces through the binding force of hydrogen bonding and strong π - π stacking, causing MB to release from the NGE surfaces. The signal changes of MB could be used to determine OTA concentration. The sensing mechanism has been studied by UV and SWV. The electrochemical processes are characterized by SWV and EIS techniques with low detection-limit (0.71 fg·mL −1 ) and a wide linear range (1 fg·mL −1 –0.1 μ g·mL −1 ). The proposed label-free aptasensor will simplify the detection processes and boost their practical applications to timely prevent OTA exposure to human bodies.